2016
DOI: 10.1364/oe.24.009955
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical response of platinum nanoparticles and platinum ions embedded in sapphire

Abstract: We report on the fabrication of sapphire samples containing platinum nanoparticles (Pt-NPs) and platinum ions (Pt-ions) and the investigation of their third-order nonlinear (NL) optical properties. The presence of Pt-NPs was confirmed by electronic microscopy and by the linear absorption spectrum that shows a localized surface plasmon band centered at 290 nm. A sample without NPs but containing Pt-ions was also studied. The absorptive and refractive contributions to the nonlinearity were studied using the z-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Many publications related to the basic characteristics of metal nanocolloids and solidstate metal composites appeared in the past years [65][66][67][68][69][70][71][72][73][74][75][76][77][78]. In the majority of the experiments the authors focused on the third-order properties of the materials.…”
Section: Optical Nonlinearity Of Spherical Nanoparticles Suspended Inmentioning
confidence: 99%
“…Many publications related to the basic characteristics of metal nanocolloids and solidstate metal composites appeared in the past years [65][66][67][68][69][70][71][72][73][74][75][76][77][78]. In the majority of the experiments the authors focused on the third-order properties of the materials.…”
Section: Optical Nonlinearity Of Spherical Nanoparticles Suspended Inmentioning
confidence: 99%
“…According to the sign of n 2 , the nonlinear refraction can be classified as self‐defocusing and self‐focusing. [ 27,157–159 ] With the increase of excitation intensity, the transmittance will increase (decrease) at first and decrease (increase) to the original intensity finally for self‐defocusing (self‐focusing), which behaves like a concave (convex) lens. As displayed in Figure 7b, typical self‐defocusing phenomenon (peak‐valley) is observed under the excitation at 532 nm.…”
Section: Tailoring Of Optical Properties Of Dielectrics By Nanoparticlesmentioning
confidence: 99%
“…In photonics, the synergistic effect between NPs and functional dielectric crystals shows significant potential for material modification with unprecedented optical phenomena, e.g., electron transfer mechanism, high‐order nonlinearity enhancement, modulation, and so on. [ 6,8,25,27 ] To promote the interaction effect between NPs and dielectrics, some well‐developed techniques have been proposed to embed NPs into the matrix for designed nanocomposite systems, such as ion beam implantation/irradiation, ion exchange, and femtosecond laser processing. [ 27–29 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of Platinum NPs in dielectric substrates with high refractive index pointed out the possibility of employing nanocomposites for designing plasmonic schemes [13]. Nevertheless, third-order nonlinear optical properties exhibited by metallic NPs seem to be strongly modulated by different parameters that depend on resonance and irradiation conditions such as pulse duration and wavelength [14]. In this direction, it has been reported that bimetallic NPs may be able to distinctively enhance the nonlinear optical response of nanosystems [15].…”
Section: Introductionmentioning
confidence: 99%